2020
DOI: 10.5603/cj.a2018.0142
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acetylsalicylic acid dosed at bedtime on the anti-aggregation effect in patients with coronary heart disease and arterial hypertension: A randomized, controlled trial

Abstract: Background: Acetylsalicylic acid (ASA) is one of the basic drugs used in the secondary prevention of coronary artery disease (CAD), and in most cases it is taken in the morning in one daily dose. It is suggested that the morning peak of platelet aggregation is responsible for the occurrence of myocardial infarctions and strokes. Hence, the aim of the study was to observe the effect of ASA (morning vs. evening) dosing on the anti-aggregative effect of platelets in patients with CAD and arterial hypertension (AH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The first finding, of a superior level of inhibition after ODevening intake of aspirin in comparison with OD-morning intake, is consistent with the results of several other studies, both in healthy subjects and patients with stable cardiovascular disease [11][12][13][14]25]. As most CVE's occur during -early morning hours [26,27], optimal platelet inhibition during these hours seems prudent.…”
Section: Discussionsupporting
confidence: 87%
“…The first finding, of a superior level of inhibition after ODevening intake of aspirin in comparison with OD-morning intake, is consistent with the results of several other studies, both in healthy subjects and patients with stable cardiovascular disease [11][12][13][14]25]. As most CVE's occur during -early morning hours [26,27], optimal platelet inhibition during these hours seems prudent.…”
Section: Discussionsupporting
confidence: 87%
“…One parallel RCT and three randomized cross-over trials reported more platelet inhibition, measured by the VerifyNow, after evening intake of low-dose aspirin compared with the standard once daily morning dosing (2, 59, 66, 67).…”
Section: Aspirin and Time Of Intakementioning
confidence: 99%
“…According to the 2016 European Guidelines on cardiovascular prevention in clinical practice, ASA prophylaxis is not recommended for subjects who do not suffer from CVD because of an increased risk of major bleeding [9]. It has also been demonstrated that time of administration strongly affects the outcome of ASA on platelet function [10]. This creates a necessity to seek alternative and safe dietary antiplatelet agents.…”
Section: Introductionmentioning
confidence: 99%